Mechanical performance of thermoplastic olefin composites reinforced with coir and sisal natural fibers: Influence of surface pretreatment. Issue 9 (25th January 2019) - Pereira, João F.; Ferreira, Diana P.; Bessa, João; Matos, Joana; Cunha, Fernando; Araújo, Isabel; Silva, Luís F.; Pinho, Elizabete; Fangueiro, Raul
Abstract : In this research, composites based on thermoplastic olefin (TPO) elastomers reinforced with natural fibers were developed, having had very interesting results, aiming toward an application in the automotive industry, for manufacturing car interior components. For the first time, sisal and coir fibers were used as reinforcement of TPO composites. The best‐performing samples have had a successfully reduced maximum elongation and improved both maximum stress and Young's modulus values. Different compositions were studied regarding several parameters: type of fiber (coir or sisal treated and nontreated), coupling agent presence (maleic anhydride grafted polypropylene [MAPP]) and fiber content. Overall, the presence of fibers has had a clear positive impact on the composites' mechanical properties, enhanced by the presence of MAPP, mostly when using 4% (w/w) of fiber content. The fibers' surface treatment was especially important in this work, enabling the evaluation of the fibers' alkali treatment's influence in the final mechanical properties of the composites. The treatment successfully removed some of the most hydrophobic constituents of the natural fibers, like lignin, improving the possibility of a better adhesion of the fibers to the matrix. Finally, the mechanical properties of the composites were evaluated, and it was concluded that the alkali pretreatment had a very positive effect on several of them, aided by the presence of MAPP. POLYM. COMPOS., 40:3472–3481, 2019. © 2019 Society of Plastics Engineers